Microbial metabolites of proanthocyanidins reduce chemical carcinogen-induced DNA damage in human lung epithelial and fetal hepatic cells in vitro. (March 2019) - Thilakarathna, W.P.D. Wass; Rupasinghe, H.P. Vasantha
Abstract: Seven selected microbial metabolites of proanthocyanidins (MMP), 3-phenylpropionic, 4-hydroxyphenyl acetic, 3-(4-hydroxyphenyl) propionic, p -coumaric, benzoic acid, pyrogallol (PG), and pyrocatechol (PC) were evaluated for their ability to reduce chemical carcinogen-induced toxicity in human lung epithelial cells (BEAS-2B) and human fetal hepatic cells (WRL-68). Cells pre-treated with MMP were exposed to a known chemical carcinogen, 4-[(acetoxymethyl) nitrosamino]-1-(3-pyridyl)-1-butanone (NNKOAc) to assess MMP-mediated cytoprotection and reduction of DNA damage. PG in BEAS-2B and PC in WRL-68 cells mitigated the NNKOAc-induced cytotoxicity. Pre-incubation of PG depicted significant protection against NNKOAc-induced DNA damage in BEAS-2B cells. PC in WRL-68 cells showed similar activity. To understand the mechanisms of PG- and PC-mediated DNA damage reduction, the effect on DNA damage response (DDR) proteins, cellular reactive oxygen species (ROS), total antioxidant capacity (TAC), glutathione peroxidase (GPx), and caspase activity were studied. PG and PC alter the DDR and may promote ATR-Chk1 and ATM-Chk2 pathways, respectively. Cellular oxidative stress induced by NNKOAc was mitigated by PG and PC through enhanced GPx expression and TAC. PG and PC suppressed the activation of the extrinsic apoptotic pathway (caspase 3 and 8) provoked by NNKOAc. MMP are beneficial in chemoprevention by reducing cellular DNA damage. Highlights: Pyrogallol and pyrocatechol-mediated cytoprotection against NNKOAc is cell line specific. Pyrogallol and pyrocatechol reduce NNKOAc-induced DNA damage in BEAS-2B and WRL-68 cells, respectively. Pyrogallol and pyrocatechol alter the DNA damage response in cells exposed to NNKOAc. DNA damage reduction by pyrogallol and pyrocatechol is contributed by the promotion of antioxidant enzymes. NNKOAc-induced caspase-3 and 8 overexpression are suppressed by pyrogallol in BEAS-2B and pyrocatechol in WRL-68 cells.